Gestão do risco de crédito das cooperativas de crédito na região sudoeste do Paraná - Monteiro, Marcelino Armindo (2014)
Credit unions are governed by the same cooperative principles but add financial functions as traditional banks. Solidarity in the financial area allows credit unions to take to their members or transferring funds spared government development of public policy in the form of credit. But it is not always clear that the "support" are returned the same way they were received, in this world of too much perfection and high competitiveness. Integrates the foreign element in the middle where you think its difficult access, lack of confidence in the fulfillment of the credit agreement contracted by creditors (cooperative). Known as credit risk or a possible non-payment of debts contracted by the cooperatives the main factor for Credit Risk Management process in cooperative institutions in the world. Thus falls the research problem, and new risk management in credit unions and a market haunted by financial crises, and if it asks: To what extent or at what point the compliance of the management of credit risk these institutions has been met? Based on this concern were traced objectives, which aim to assess the practices of risk management in credit unions Southwest of Paraná (PR) according to the resolutions of the National Monetary Council (CMN). For this, one has the following specific objectives: List the risk management practices needed to grant credit; Identify how they are being addressed management practices of credit risk considering CMN standard; Ascertain the impact of the management of risk perceived by managers in credit unions; Rise in quantitative terms as these cooperatives lost annually in default; Compare practices of cooperatives surveyed each other and with the resolutions of the CMN. The work is justified by the importance of the risk management process for cooperative institutions, academia and the contribution to the reinforcement to what the CMN has been recommended in its resolutions. And to achieve the desired results a study of multiple case was applied in cooperative CRESOL, SICOOB and SICREDI / PR, with qualitative and quantitative approach in part with secondary and primary data. The secondary data were collected by reviewing the literature pertaining to the areas of cooperative movement in general and credit risk management and credit standards and CMN resolutions on the topic, also collected in the Financial Reports of the three Credit unions. Primary data were collected through a questionnaire in these institutions, being interviewed Managers of Credit, Senior Advisor of the Comptroller, Assessor and Supervisor of Credit. And the data obtained were compared to the information of the respondents from the same institution and then with the other, in the data analysis of the same names (institutions) are no longer quoted and was assigned the name of CASE (case1 case2 and 3). A concern with risk management in these institutions was identified. Also noticed that credit is only been released when passing by analysis of at least three people. There are procedures for credit analysis that follows all the necessary limits for the proposal to be granted and are evaluated according to the income of the applicant and the individual cooperatives are classified according to their Wealth of References (PR in Portuguese) and Heritage References Required (PRE in Portuguese), to receive credit of their plants and up to release credit to their members Corporations if any. Yet losses were located some steeper others do not. Realize that there are still smaller studies on risk management in credit unions, given the situation they were in the same, but is currently worth strengthen research to know how these institutions deal with the management of credit risk and other risks.